Konseling Lintas Budaya pada Kasus Kesulitan Asertif: Studi Kasus Mahasiswa dalam Konteks Budaya Jawa - Nurli Hayati; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This This study aims to examine the effectiveness of cross-cultural counseling in addressing assertiveness difficulties in subject SH within the Javanese cultural context. The research employed an experimental approach using assertive training as the analytical technique to enhance the subject’s assertiveness skills. Data were collected through in-depth interviews with SH, a student from a Javanese cultural background who exhibited a pattern of being overly accommodating. The findings indicate that the overly accommodating behavior experienced by SH cannot be separated from Javanese cultural values such as politeness, unggah-ungguh, tepa selira, and the maintenance of social harmony. These values, which initially functioned as positive internalization, became maladaptive when practiced excessively, causing SH to have difficulty refusing requests, setting personal boundaries, and becoming vulnerable to stress, fatigue, and emotional strain. The social environment, which tended to rely on SH, further reinforced this behavioral pattern. The cross-cultural counseling intervention applied integrated assertiveness training and cognitive restructuring while respecting Javanese cultural norms. The findings show that cross-cultural counseling helped SH understand that cultural values can be upheld without compromising personal well-being. The counselor’s multicultural competence was a determining factor in adapting intervention strategies to align with the client’s sociocultural context. Based on these results, the effectiveness of cross-cultural counseling is determined by the counselor’s cultural awareness, orientation toward diversity, and the selection of relevant techniques such as assertive training. Recommendations for SH include gradual assertiveness practice, establishing personal boundaries, emotional regulation, and daily reflection to achieve a balance between maintaining social relationships and psychological well-being.